Manajemen Strategi Dinas Sosial Dalam Penanggulangan Kemiskinan Ekstrem Di Kabupaten Karawang - Debby Intan Suci Rahmawati; Eka Yulyana; Rahman Rahman (Jurnal Ilmiah Wahana Pendidikan, 2022)
Research on Strategic Management of Social Services in Reducing Extreme Poverty in Karawang Regency is motivated by the determination of extreme poverty in Karawang Regency by the central government, which then causes a lot of controversy considering Karawang Regency is one of the areas with great natural potential and then as the area with the second largest Minimum Wage in Indonesia. This study aims to analyze and determine the object of research that is studied using the strategy management theory of Fred R. David (2011) which has three dimensions, formulation, implementation and evaluation. This research is qualitative. The results of research and discussion data show that strategic management in dealing with extreme poverty carried out by the Social Service has not been optimal, this is reinforced starting from the formulation dimension with the lack of formulation of long-term oriented strategic plans and the inability of the Social Service to identify initial problems, then the implementation dimension where the distribution of assistance uneven social distribution and evaluation dimensions which show that the Social Service does not reconstruct existing mistakes by taking corrective steps.